UIN Walisongo Green Campus Study: Implementation of Education Readiness in The Faculty of Science and Technology - Bunga Ihda Norra; Anif Rizqianti Hariz (Program Studi Pendidikan Kependudukan dan Lingkungan Hidup, 2022)
This study investigated the level of readiness and any difficulties to developing a green campus at UIN WALISONGO, especially in the field of education. This mixed-method study requires data on both processes and outcomes. The information was a grade for faculty preparation in education according to UI Green Matric standard, and limitations in the faculty environment towards the green campus. The preparedness score was 3.6. level 3 means the faculty is ready but must solve various issues. Obstacle to developing a green campus include the absence of fair distribution of socialization from faculty to various levels and a lack of sustainability courses in most study programs. The faculty lacks a sustainability group that work under the dean. The faculty hopes to green the campus by maximizing the academic community.